Memoir, Correspondence, and Miscellanies, From the Papers of Thomas Jefferson, Volume 4 - Jefferson, Thomas, 1743-1826; Randolph, Thomas Jefferson, 1792-1875 (Salt Lake City, UT : Project Gutenberg, 2005)
"Memoir, Correspondence, and Miscellanies, From the Papers of Thomas Jefferson" edited by Thomas Jefferson Randolph is a collection of historical documents written in the early 19th century. This compilation contains letters and writings by Thomas Jefferson himself, detailing various personal, political, and philosophical thoughts during his time as a statesman. The themes throughout the opening letters range from concerns about political decisions affecting the United States to reflections on personal relationships. At the start of the volume, Jefferson writes to various correspondents, including government officials and personal friends, discussing topics such as the significance of maintaining the integrity of the U.S. Constitution, the complexities surrounding governance, and matters related to foreign relations, particularly with France and Spain. His letters reveal a mixture of political strategy and personal sentiment, specifically his desire for transparency in governmental actions and the importance he places on friendship and trust within political spheres. Jefferson's clear advocacy for cautious governance, respect for constitutional boundaries, and his insights into the political landscape of his time provide an engaging entry into the world of early American politics. (This is an automatically generated summary.)
Release date is 2005-09-30
Produced by David Widger
Keywords: United States -- Politics and government -- 1775-1783; United States -- Politics and government -- 1783-1865